Desarrollo de un aplicativo web y móvil para la clínica veterinaria “Animal Home” ubicada en la ciudad de Latacunga - Alvarado Tualombo, Kevin Paul (2022)
The actual titling project was performed at the "Animal Home" Veterinary Clinic, located at Av. Unidad Nacional, Las Bethlemitas sector, Latacunga city, where, through the application field research techniques, such as interview, survey, observation, it was identified, what the inadequate processes are generated into administration for the medical appointments control and registration, further, the medical records mishandling, other hand, it does not have the telemedicine service The actual titling project was performed at the "Animal Home" Veterinary Clinic, located at Av. Unidad Nacional, Las Bethlemitas sector, Latacunga city, where, through the application field research techniques, such as interview, survey, observation, it was identified, what the inadequate processes are generated into administration for the medical appointments control and registration, further, the medical records mishandling, other hand, it does not have the telemedicine service and inventory management service, these actions are generated, manually into agendas, files and notebooks, which causes a time greater investment, for this reason, it is raised the need to generate a technological proposal for the web and mobile application development for the "Animal Home" veterinary clinic. For its conception was used qualitative and inductive research methodologies, in order to publicize the problem and identify the primary needs. For project performance was used software tools, such as the Django Framework, which is based on the Python Language, JavaScript, PostgreSQL, Java, by applying the agile Scrum methodology for web environment and the Mobile-D methodology for mobile environment, at the same time, was used the Unified Modeling Language for diagram design. As a result, it was got the web and mobile application implementation in the veterinary clinic, at highlighting the virtual assistant functionality for telemedicine, favorably, optimizing resources, such as personal time, and investment to improve the veterinary clinic management